On extremal trees with respect to the F-index - Abdo, Hosam; Dimitrov, Darko; Gutman, Ivan (Kuwait Journal of Science, 2017)
In a study on the structure--dependency of the total $π$-electron energy from 1972,Trinajsti\'c and one of the present authors have shown that it depends on the sums$\sum_{v\in V}d(v)^2$ and $\sum_{v\in V}d(v)^3$, where $d(v)$ is the degree of a vertex $v$ of the underlying molecular graph $G$. The first sum was later named {\it first Zagreb index}and over the years became one of the most investigated graph--based molecularstructure descriptors. On the other hand, the second sum, except in very fewworks on the general first Zagreb index and the zeroth--order general Randi\'c index, has been almost completely neglected. Recently, this second sum was named{\it forgotten index}, or shortly the $F$-index, and shown to have anexceptional applicative potential. In this paper we examine the trees extremal with respect to the $F$-index